The multisystemic roots of South African child and youth resilience: A scoping review - Linda C. Theron; Adrian D. van Breda (PLoS ONE, 2025)
Introduction and objective A multisystemic approach to researching resilience investigates resources across multiple systems, including biological, psychological, social, institutional, structural, environmental, and cultural systems, with special interest in how these resources co-act to enable better-than-expected outcomes among risk-exposed children and youth. This approach is an important step toward redressing neoliberal misinterpretations of resilience as a personal capacity. However, it is unclear how well a multisystemic approach is reflected in recent studies of child and youth resilience conducted in South Africa, a country where ongoing structural violence demands resilience from most children and youth. In response, this article reports a scoping review of South African child and youth resilience studies published between 2018 and 2023. Methodology The methodology aligned with the PRISMA extension for Scoping Reviews. The authors systematically scoped the available literature ( n = 1309 records) to determine which resources from which systems were associated with the resilience of South African children and youth (birth to 29 years). Using a multisystem resilience framework, the narrative review of 99 eligible studies documents the biological, psychological, social, institutional, structural, environmental and cultural resources that enabled better-than-expected outcomes among risk-exposed children and youth. Results Psychological and social resources were more prominently reported than biological, institutional, structural, environmental or cultural resources. Two-thirds of the included studies reported resources from two or more systems, with psychological and social systems dominating multisystem studies. Despite the inclusion of multiple systems, studies seldom reported co-acting resources. Discussion Although the attention to resources across multiple systems is encouraging, child and youth resilience agendas will be better served by studies that document co-acting resources. This will allow policymakers and service providers to gauge the additive effects of multiple resources and which combinations of resources are most likely to advance young people’s resilience.